Study on the Effects of Tannase on the De Astringency of Pomegranate Juice - Guida Zhu; Longwen Wang; Han Wang; Zihan Chen; Xue Li; Yi Ji; Jing Yu; Ping Song (Foods)
Reducing the punicalagin content is an effective strategy for eliminating the astringency of pomegranate juice. In this study, pomegranate juice was used as the raw material, and tannase was applied to convert punicalagin into ellagic acid and gallic acid. The effects of tannase concentration, reaction time, and temperature on juice deastringency were evaluated, along with the antioxidant and physicochemical properties of the treated juice. The results demonstrated that, under optimal conditions (33.9 U/100 mL tannase, 30 °C, 90 min reaction time), the punicalagin content decreased by 27.8%, while the ellagic acid and gallic acid levels increased by 24.2% and 32.3%, respectively, effectively reducing the juice’s astringency. Under these conditions, the total phenolic content reached 110 mg/100 g, with a free radical scavenging capacity of 69.8%, significantly enhancing the juice’s antioxidant properties. These results suggest that tannase treatment of pomegranate juice enhances the polyphenol content, thereby improving its health benefits without compromising the product quality.